Micropropagacion in vitro del pasto Brachiaria brizanta cv. marandu - Gomez Kosky, R.=700 1 Cabrera Facio, A.; Garcia Rodriguez, L.
(En, Es)
Ilus., 3 ref.
Keywords: BRACHIARIA BRIZANTHA; MICROPROPAGACION; CULTIVO IN VITRO; PASTIZALES; CUBA; BRACHIARIA MARANDU